2015
DOI: 10.1155/2015/545674
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hair Aluminum, Lead, and Mercury in a Sample of Autistic Egyptian Children: Environmental Risk Factors of Heavy Metals in Autism

Abstract: Background and Aims. The etiological factors involved in the etiology of autism remain elusive and controversial, but both genetic and environmental factors have been implicated. The aim of this study was to assess the levels and possible environmental risk factors and sources of exposure to mercury, lead, and aluminum in children with autism spectrum disorder (ASD) as compared to their matched controls. Methods. One hundred ASD children were studied in comparison to 100 controls. All participants were subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 33 publications
5
51
0
4
Order By: Relevance
“…Higher levels of aluminum were observed in the hair [45,46,47] and urine [48] of children with ASD, compared to children without ASD. One study from Egypt additionally found that the level of aluminum in children’s hair was positively correlated with the use of aluminum pans in the home [45]. However, some studies found no association between aluminum level in hair [49,50] and aluminum level in blood and urine of children with ASD [51].…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of aluminum were observed in the hair [45,46,47] and urine [48] of children with ASD, compared to children without ASD. One study from Egypt additionally found that the level of aluminum in children’s hair was positively correlated with the use of aluminum pans in the home [45]. However, some studies found no association between aluminum level in hair [49,50] and aluminum level in blood and urine of children with ASD [51].…”
Section: Introductionmentioning
confidence: 99%
“…To track the sources of the metals they concluded that mercury, lead, and aluminum levels were positively correlated with maternal fish intake, residence near gasoline stations, and use of aluminum pans, respectively. 34 Another study conducted on 60 children (ASD=30 and controls=30), researchers got strong association and significant difference in the lead, mercury and cadmium concentrations between ASD and control. 35 Yassa, 2014 conducted a research on blood and hair samples obtained from 45 children with autism and 45 children served as controls between the ages of 2 and 10 years to find out exposure variation to lead and/or mercury as heavy metals.…”
Section: Discussionmentioning
confidence: 98%
“…Also, none can deny the impact of increased awareness all over the world about how to pick autistic manifestations as well as the negative influence of exposure to some environmental hazards on such significant rise of ASD prevalence [12].…”
Section: Prevalence and Gender Differencesmentioning
confidence: 99%